2012
DOI: 10.1152/ajprenal.00418.2011
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of the PGE2 synthetic system in the kidney is associated with the time frame of renal developmental vulnerability to cyclooxygenase-2 inhibition

Abstract: Pharmacological blockade of cyclooxygenase-2 (COX-2) causes impairment of kidney development. The present study was aimed at determining temporal expression pattern and activity of the PGE(2) synthetic pathway during postnatal nephrogenesis in mice and its association to the time window sensitive to COX-2 inhibition. During the first 10 days after birth, we observed transient induction of mRNA and protein for microsomal PGE synthase (mPGES)-1 between postnatal days 4 (P4) and P8, but not for mPGES-2 or cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…Most PG were continuously synthesized during incubation (Fig. 4 A), which is consistent with the high level of PG synthesis during kidney homogenate incubation [12, 21, 36]. Similar to PG increase in non-fixed tissue (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Most PG were continuously synthesized during incubation (Fig. 4 A), which is consistent with the high level of PG synthesis during kidney homogenate incubation [12, 21, 36]. Similar to PG increase in non-fixed tissue (Fig.…”
Section: Resultssupporting
confidence: 80%
“…10 The contribution of PGE 2 to regulation of cell cycle in healthy and injured renal cells has been described 16,[33][34][35][36] but not in the PT. Our work showed that PGE 2 and SLP inhibit the cell cycle in MCT cells similar to TGFβ, reducing both protein and DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 and EP receptors including EP4 play important roles in kidney development, as suggested by a reduced glomerular size in EP4-deficient mice (Frolich et al, 2012). In vitro, PGE 2 acting via EP4 receptors augmented the survival of glomerular epithelial cells deprived of serum (Aoudjit et al, 2006), and an EP4 receptor agonist stimulated proliferation and decreased apoptosis of renal epithelial cells (Yamamoto et al, 2010).…”
Section: Kidneymentioning
confidence: 99%